A study of automated teller machine design via context-based user experience - Yau, Wing Tak (2014)
With a market maturing, business environment has become highly competitive where product function, quality will no longer guarantee the success of a product. To be distinguished in the market, a new value of product dimensions – user experience (UX) should be considered and added into the product during product design and development process. Nevertheless, the most tedious part within the entire design process is to deal with user experience, which is known as complex, dynamic and subjective. Therefore it is necessary to investigate user experiences from a contextual level. After reviewing some contextual user experience analysis tools, it was found that only a few of them address the problem of individual difference during the user experience evaluation process. This project attempts to fill this gap by proposing a Scenario Co-build System (SCS) as a tool to evaluate user experience from a contextual level and apply this methodology on a case study, Wincor Nixdorf ProCash Automated Teller Machine (ATM). Market research was conducted as a pre-study for the basic understanding of ATM usage contexts as well as data collection for the assistance of SCS contextual settings.